Evaluation of Some Herbicides for Weed Control in Wheat (Triticum aestivum L.) in Northern Sudan - Idris, Khogali, I.; Mohamed, Elsadig S. (University of Khartoum Journal of Agricultural Sciences, 2023)
A field trial was conducted at Hudeiba Research Station Farm, River Nile State, Sudan, during 2001/2002, 2002/2003 and 2003/2004 winter seasons. The objective was to evaluate the activity and selectivity of three pre-emergence herbicides for weed control in wheat. The herbicides treatments were pendimethalin (Stomp) at 1.2, 1.8 and 2.4 kg a.i. ha-1 , oxyfluorfen (Goal) at 0.24, 0.36 and 0.48 kg a.i ha -1 and oxadiazon (Ronstar) at 0.72, 1.08 and 1.44 kg a.i ha -1 . The prevailing weed species in the experimental sites were Ipomoea sp, wild mustard (Sinapis arvensis L.), common beet (Beta vulgaris L.), sweet signal grass [Brachiaria eruciformis (Sm)] and Bermuda grass [Cynodon dactylon (L.) Pers.]. The results showed that the losses in grain yield of wheat, due to weeds competition, were 37%, 29% and 21% for seasons 2001/2002, 2002/2003 and 2003/2004, respectively. The herbicide pendimethalin, at all rates tested, showed no phytotoxicity symptoms on wheat. The higher rates of oxadiazon and oxyfluorfen, however, showed slight phytotoxicity to the wheat crop. All herbicide treatments of Ronstar and Goal resulted in good to excellent control (72%–97%) of both grassy and broad-leaved weeds. The herbicide pendimethalin displayed excellent activity against grasses and poor to satisfactory activity (0%-67%) against broad-leaved weeds. The weed Cynodon dactylon tolerated all herbicide treatments. With the exception of Stomp, all herbicide treatments significantly increased wheat grain yield compared to the weedy check.